Symptomatic postoperative discal pseudocyst following percutaneous endoscopic lumbar discectomy: A case report and review of the literature. Issue 3 (22nd January 2021) - Li, Junjie; Liang, Shuhan; Xie, Wei; Luo, Jinxin; Tang, Jin; Liu, Liu; Li, Ying; Wu, Congjun; Li, Xugui
Abstract: Rationale: Percutaneous endoscopic lumbar discectomy (PELD) is an effective treatment for lumbar disc herniation and postoperative discal pseudocyst (PDP) can rarely develop after PELD. Patient concerns: A 30-year-old man experienced low back pain and pain in the right lower extremity for 1 month, which aggravated for 3 days. Diagnoses: Preoperative CT and MRI showed lumbar disc herniation at the L4/5 level. Then the patient underwent PELD under local anesthesia and his symptoms disappeared immediately after surgery. After 37 days of PELD, the patient complained of recurrent low back pain on the right side, and pain on the outer side of his lower leg. MR imaging revealed cystic mass with low signal on T1-weighted images (T1WI), and high signal on T2-weighted images (T2WI). The patient was diagnosed with a symptomatic PDP after PELD. Interventions: Initially, the patient was treated with conservative treatment, including administration of aescin and mannitol by intravenous infusion, physical therapy, sacral canal injection. Then he underwent discography at L4/5 and ozone ablation under local anesthesia. Outcomes: The patient's condition improved significantly after 1 week of surgery and was discharged. One-year and 3-month follow-up revealed no recurrence of low back pain and leg pain. Lessons: PDP is one of the rare complications of PELD, usually occurs in young patients. Patients with PDP have a low signal intensity on T1WI and high signal intensity on T2WI, which can be treated by conservative treatment, interventional therapy, and surgical treatment.